Effect of Investment, Free Cash Flow, Earnings Management, Interest Coverage Ratio, Liquidity, and Leverage on Financial Distress - Eddy Suranta; Muhammad Alif Bimo Satrio; Pratana Puspa Midiastuty (Ilomata International Journal of Tax and Accounting, 2023)
This study aims to provide empirical evidence of the effect of investment, free cash flow, earnings management, interest coverage ratio, liquidity and leverage on financial distress. The dependent variable is financial distress as measured by the Altman Z-score. The independent variables are total assets growth as a proxy for investment, free cash flow, earnings management with modified Jones model, interest coverage ratio, leverage and liquidity. This study was tested using ordinal logistic regression analysis. The sample used in this study were manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The sample in this study was selected using purposive sampling with a total of 392 observations. The results of this study indicate that free cash flow, interest coverage ratio and liquidity have a significant effect on financial distress, while investment, earnings management and leverage have no effect on financial distress. The implication of this research is to prove the signal theory and agency theory. The limitation of this study is that there are still errors of type I and II in classifying companies that experience financial distress and non-financial distress